LAW ENFORCEMENT AGAINST AIR POLLUTION SIYASAH TANFIDZIYAH PERSPECTIVE (CASE STUDY IN PAREPARE CITY): PENEGAKAN HUKUM TERHADAP PENCEMARAN UDARA PERSPEKTIF SIYASAH TANFIDZIYAH (STUDI KASUS DI KOTA PAREPARE) - Sukri, Indah (Constitutional Law Society, 2025)
Through Parepare City Regional Regulation No. 2 of 2011 concerning Environmental Protection and Management, to further guarantee legal certainty and provide protection for everyone's right to a good and healthy living environment as part of the protection of the entire ecosystem, it is necessary to carry out appropriate environmental management. can maintain and preserve environmental functions. as implementation of Law no. 32 of 2009 concerning Environmental Protection and Management. The purpose of this research is to analyze Law Enforcement Against Air Pollution in Parepare City from the Siyasah Tanfidziyah Perspective. The research approach used in this research is a qualitative approach, with the type of research used being empirical juridical research, with descriptive qualitative data. Using environmental law enforcement theory, and Siyasah Tanfidziyah. The results of this research show that the impact of air pollution resulting from the tire retreading business in Parepare City has a negative impact on the community around the business location. The negative impact felt by the community around the business location is that every day they breathe unhealthy air due to smoke and community activities. disrupted, the law enforcement process regarding air pollution in Parepare City carried out by Parepare City DLH cannot be said to be upheld, because several factors in determining the enforcement of a law are influenced by the effectiveness of law enforcement. In determining whether law enforcement is effective or not it is influenced by several factors. namely law enforcement factors, facilities or facilities factors, and community factors. And referring to the perspective of siyasah tanfidziyah towards law enforcement, looking at several factors from law enforcement theory and environmental theory it cannot be said to be effective because based on the perspective of siyasah tanfidziyah theory there are still many factors that have not been implemented properly in accordance with the instructions in the Al-Quran.